Do Ecotourism Responsibilities And Principles Influence Green Business Behavior? Gorontalo Regency Religious Tourism Study - Nugroho, Moh Agus; Amin, Sirajudin; Ainun, Umu (ITB AAS INDONESIA Surakarta, 2024)
This research examines the variables influencing the performance of religious tourism managers in Bongo Village, Gorontalo Province, on Green Business Behavior in ecotourism. The variables used to measure the performance of tourism managers are attitudes towards Ecotourism Responsibility and Ecotourism Principles observed in the tourism site conditions. The assessment is conducted by visitors or tourists. The study employs probability sampling, and there were 155 respondents involved in the research. The analytical technique used in this study is path analysis to determine the relationships/effects between variables. It is concluded that the variable of Ecotourism Responsibility does not have a significant influence on Green Business Behavior. Similarly, the variable of Ecotourism Principles also does not affect Green Business Behavior